Implementasi Metode Teams Games Tournament (TGT) dalam Pembelajaran Al-Ājrūmiyyah dan Pengaruhnya Terhadap Motivasi Belajar Santri PP Al-Fadhilah Maguwoharjo - Dwi Rahmawati (Mahira: Journal of Arabic Studies & Teaching, 2023)
The purpose of this study was to determine the application and influence of the Teams Games Tournament (TGT) method in learning Al-Ājrūmiyyah on learning motivation. This study uses the Pre-Experimental Designs type of One-Group Pretest Posttest Design with the object of research the Teams Games Tournament (TGT) method and the research subjects are Al-Ājrūmiyyah class, totaling 64 students. Meanwhile, to analyze the data, researchers used quantitative descriptive analysis methods. The hypothesis test used is a non-parametric statistical test, namely the Mann Whitney U Test. The results show: first, the implementation of the Teams Games Tournament (TGT) learning method in Al-Ājrūmiyyah learning includes a) learning preparation such as preparing worksheets, preparing games and tournaments, b) implementing learning activities in the form of class presentations and group discussions, c) evaluation or deepening the material, namely the implementation of games, tournaments and teams recognize. Second, the implementation of the Teams Games Tournament (TGT) learning method has an effect on Al-Ājrūmiyyah's learning motivation. Based on the hypothesis test, the Asymp value was obtained. Sig of 0.000 <0.05, it indicates a significant difference between pre-action and post-action. The results of data analysis show that the percentage of students' learning motivation has increased after the implementation, from 53.98% in the Moderately Motivated category to 77.7% in the Very Motivated category